AN ANALYSIS OF THE CHALLENGES AND STRATEGIES OF ENGLISH LANGUAGE TEACHING AT UPT SMPN SATU ATAP KEBUN TINGGI, KECAMATAN KAMPAR KIRI HULU, KABUPATEN KAMPAR, PROVINSI RIAU - Mareti; Melyan Melani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
English language teaching in rural schools often encounters substantial challenges that hinder effective learning. This study investigates the challenges and strategies of English language teaching at UPT SMPN Satu Atap Kebun Tinggi, located in Kampar Kiri Hulu Subdistrict, Kampar Regency, Riau Province. A qualitative descriptive approach was employed, with data collected through in-depth interviews involving four key informants (an English teacher, a student, a school management staff member, and the vice principal), classroom observations, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, supported by methodological triangulation to ensure credibility. The findings indicate four major challenges: inadequate learning facilities, students’ low self-confidence in using English, geographical barriers affecting school access, and a shortage of qualified English teachers. To address these challenges, the school implemented several strategies, including continuous teacher professional development, adaptive use of available technology, and collaboration with local government and the community. These strategies helped sustain English learning activities despite existing limitations, highlighting the importance of contextual and integrated support for improving English language teaching in rural education settings.